Reação tecidual e detecção de Interleucina-6 promovida por cimentos à base de silicato de cálcio no subcutâneo de ratos - Saraiva, Juliana Alcarás [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
We evaluated the tissue reaction promoted by MTA Plus, MTA Fillapex, AH Plus and Endofill in the rat subcutaneous. Polyethylene tubes filled with MTA Plus, MTA Fillapex, AH Plus or Endofill were implanted in the rat subcutaneous. In the control group (CG), empty tubes were implanted. After 7, 15, 30 and 60 days, the tubes surrounded by connective tissue were paraffin-embedded. In HE-stained sections, the volume density of inflammatory cells (VvIC) and fibroblasts (VvFb) was estimated in the capsules. Immunohistochemistry (IH) for interleukin-6 (IL-6) was performed, and the number of IL-6-immunolabeled cells was obtained. The birefringent collagen content was quantified in picrosirius-red-stained sections under polarized light. Data were analyzed by ANOVA and Tukey tests (p≤0.05). At 7 days, capsules showed moderate inflammatory reaction, and VvIC and IL-6-immunolabeled cells were similar either in the capsules adjacent to the sealers or in CG. In all groups, VvIC and IL-6 IH reduced significantly from 7 to 60 days. At 60 days, IL-6 IH was reduced significantly in MTA Plus and MTA Fillapex in comparison to AH Plus; no difference was found in the VvIC among MTA Plus, MTA Fillapex, AH Plus and CG whereas Endofill exhibited the highest VvIC. The reduction in VvIC was parallel to an increase in the collagen content in the capsules of in all groups, except Endofill. MTA Plus, MTA Fillapex and AH Plus induce a response that culminates in the regression of inflammation and formation of a fibrous capsule over time. Considering that IL-6 immunoexpression significantly reduced in the MTA Plus and MTA Fillapex groups, it is possible to suggest that these endodontic sealers may favor the regression of the periapical lesion.

O objetivo deste estudo foi avaliar a reação tecidual promovida pelos cimentos endodônticos MTA Plus e MTA Fillapex em comparação ao AH Plus, usado como padrão “ouro”, e ao Endofill, considerado como controle positivo, no subcutâneo de ratos. Foram utilizados 100 animais e em cada foi inserido no tecido subcutâneo dorsal um tubo de polietileno preenchido com MTA Plus, MTA Fillapex, AH Plus, Endofill ou vazio (grupo controle). Após 7, 15, 30 e 60 dias, os tubos implantados e os tecidos circundantes foram removidos, fixados e incluídos em parafina. Nos cortes corados com HE, a densidade de volume de células inflamatórias (VvCI) e fibroblastos (VvFb) foi estimada nas cápsulas. Imuno-histoquímica para detecção de interleucina-6 (IL-6) foi realizada e a densidade numérica de células imunopositivas foi computada. O conteúdo de colágeno birrefringente nas cápsulas foi quantificado nos cortes corados com picrosirius e analisados sob luz polarizada. Os dados foram analisados pelo ANOVA e teste de Tukey (p≤0,05). Aos 7 dias, as cápsulas apresentaram reação inflamatória moderada. Em todos os grupos, a VvCI e as células imunopositivas para IL-6 reduziram significantemente de 7 para 60 dias. Aos 60 dias, o número de células imunopositivas para IL-6 foi significantemente reduzido nos grupos MTA Plus e MTA Fillapex em comparação ao AH Plus; diferenças significantes na VvCI entre MTA Plus, MTA Fillapex, AH Plus e grupo controle não foram observadas, enquanto que o Endofill exibiu a maior VvCI. A redução da VvCI foi paralela ao aumento do conteúdo de colágeno nas cápsulas de todos os grupos, exceto no Endofill. Portanto, o MTA Plus, MTA Fillapex e AH Plus induziram uma resposta que culmina na regressão da inflamação e formação de uma cápsula fibrosa com o decorrer do tempo. Considerando que a imunoexpressão para IL-6 reduziu significativamente nos grupos MTA Plus e MTA Fillapex, é possível sugerir que estes cimentos endodônticos possam favorecer a regressão da lesão periapical.
Tissue reaction and detection of interleukin-6 promoted by calcium silicate based sealers in rat subcutaneous
Keywords: Materiais biocompatíveis; Teste de materiais; Endodontia; Histologia; Interleucina-6; Colágeno; Biocompatible materials; Materials testing; Endodontics; Histology; Interleukin-6; Collagen